2020
DOI: 10.1371/journal.pgen.1008723
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversification of Paramecium Ku80 paralogs safeguards genome integrity during precise programmed DNA elimination

Abstract: Gene duplication and diversification drive the emergence of novel functions during evolution. Because of whole genome duplications, ciliates from the Paramecium aurelia group constitute a remarkable system to study the evolutionary fate of duplicated genes. Paramecium species harbor two types of nuclei: a germline micronucleus (MIC) and a somatic macronucleus (MAC) that forms from the MIC at each sexual cycle. During MAC development, 45,000 germline Internal Eliminated Sequences (IES) are excised precisely fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 61 publications
4
36
0
Order By: Relevance
“…To quantify the effects of SPT16-1 KD on IES retention, we used sequencing data from non-silenced autogamous cells of the same strain, as a control [24]. Excision of all IESs is altered and 98.6% (44,334) IESs are statistically significantly retained in the developing MAC after SPT16-1 KD, similar to the 99% (44,491) observed after PGM KD [36] (S7 Fig). We measured IES retention at each IES boundary, using the boundary score method [36].…”
Section: Spt16-1 Is Essential For Programmed Genome Rearrangementsmentioning
confidence: 58%
See 1 more Smart Citation
“…To quantify the effects of SPT16-1 KD on IES retention, we used sequencing data from non-silenced autogamous cells of the same strain, as a control [24]. Excision of all IESs is altered and 98.6% (44,334) IESs are statistically significantly retained in the developing MAC after SPT16-1 KD, similar to the 99% (44,491) observed after PGM KD [36] (S7 Fig). We measured IES retention at each IES boundary, using the boundary score method [36].…”
Section: Spt16-1 Is Essential For Programmed Genome Rearrangementsmentioning
confidence: 58%
“…tetraurelia , a specialized Ku70/Ku80 heterodimer acts upstream of DNA cleavage, instead of downstream. Indeed, the depletion of the developmental-specific Ku80 paralog Ku80c abolished DNA cleavage at IES ends, resulting in retention of all IESs in the new MAC [ 16 , 44 ], as for Spt16-1 and Pgm depletion. Furthermore, similar to Spt16-1 being essential for Pgm nuclear localization, Ku80c is required for anchoring the Pgm endonuclease in the developing MAC [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…IESs are invariably bounded by two 5 0 -TA-3 0 dinucleotides, one of which is left at the junction in the MAC genome after excision. IES excision in the developing MAC is initiated by DNA double-strand breaks at IES ends by the endonuclease PiggyMac (Pgm) assisted by other proteins, which are likely part of the excision machinery or interact with it [6][7][8][9]. Despite significant progress in characterization of the mechanisms underlying IES elimination, the evolutionary origin of IESs remains mysterious.…”
Section: Introductionmentioning
confidence: 99%
“…The Ku70a/80c heterodimer co-purifies with PiggyMac and is essential for the licensing of its endonuclease [ 169 ]. Recently, immunofluorescence microscopy and high-throughput DNA sequencing revealed that Ku80c stably anchors the PiggyMac (Pgm) endonuclease through an interaction on the α/β domain of Ku80c [ 170 ]. The ciliate model suggests a tight coupling between DSB introduction and repair with a central role of Ku [ 171 ].…”
Section: A Well-conserved Gene Along Evolutionmentioning
confidence: 99%